2016
DOI: 10.1038/srep29134
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deposition may enhance soil carbon storage via change of soil respiration dynamic during a spring freeze-thaw cycle period

Abstract: As crucial terrestrial ecosystems, temperate forests play an important role in global soil carbon dioxide flux, and this process can be sensitive to atmospheric nitrogen deposition. It is often reported that the nitrogen addition induces a change in soil carbon dioxide emission in growing season. However, the important effects of interactions between nitrogen deposition and the freeze-thaw-cycle have never been investigated. Here we show nitrogen deposition delays spikes of soil respiration and weaken soil res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 61 publications
3
7
0
Order By: Relevance
“…Short-term environmental perturbations often have large impacts on biogeochemical rate measurements. For example, as seen in this microcosm experiment and in field studies, N pulse deposition decreased respiration, while water addition stimulated respiration (28,(48)(49)(50). However, results from this study and other studies (51, 52; B. Steven and C. R. Kuske, submitted for publication) suggest that biogeochemical flux responses to short-term environmental perturbations may be invoked by highly complex responses and/or mechanisms not represented by conventional genomic markers.…”
Section: Discussionsupporting
confidence: 42%
“…Short-term environmental perturbations often have large impacts on biogeochemical rate measurements. For example, as seen in this microcosm experiment and in field studies, N pulse deposition decreased respiration, while water addition stimulated respiration (28,(48)(49)(50). However, results from this study and other studies (51, 52; B. Steven and C. R. Kuske, submitted for publication) suggest that biogeochemical flux responses to short-term environmental perturbations may be invoked by highly complex responses and/or mechanisms not represented by conventional genomic markers.…”
Section: Discussionsupporting
confidence: 42%
“…In contrast, N addition increased organic C pools in surface soils of QM, which agrees with several previous studies in China [44][45][46] . N is often the limiting nutrient in Northeast China, low levels of N addition generally increase plant production and the accumulation of soil organic matter, thus increasing the forest C sequestration [47] .…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the N 2 O flux, the pulse of CO 2 flux from soils during thaw became much weaker and no obvious flush CO 2 flux was even reported by Rong et al (2015) in cropland and grassland. The maximum rates of soil CO 2 flux during thaw in this study (Supplementary Table S2) was within the reported values of 10-151 mg C m -2 h -1 in spruce and Korean pine forest lands (Wu et al, 2010;Yan et al, 2016). Considering the absence of peak flux in the field observation, the incipient rates of N 2 O and CO 2 fluxes calculated in this study (Figs 2 and 4) would be appropriate to represent the magnitude of N 2 O and CO 2 flush fluxes following spring soil thawing.…”
Section: Discussionsupporting
confidence: 56%